THE IMPORTANCE OF FUNCTIONAL TRAINING IN THE ATHLETE TRAINING SYSTEM - Arabboyev Qahramon Tohirjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In order to improve the level of high performance achieved by today’s athletes, the article talks about the improvement of the training methods of highly qualified athletes and the functional training and its essence and importance in the training of athletes. Also, the authors focused on the main characteristics of functional training and control of functional systems.